Pelatihan Teknik Pemanenan Jamur Tiram untuk Meningkatkan Keterampilan Karang Taruna Desa Codo Kab. Malang - Maria Intan Kumala; Alif Anas Sobirin (Educational Consultant & Counseling Career (EC3) Mataram, 2024)
Oyster mushrooms are known as one of the food products with high economic value, easy to cultivate, and have significant health benefits. Karang Taruna in Codo Village as a youth organization provides great opportunities for developing village potential. Improving skills in oyster mushroom harvesting techniques is expected to provide new insights for Karang Taruna members in developing their businesses. The training implementation method is carried out using a theoretical approach. To ensure participant understanding, the training ended with an evaluation and feedback session. The training was conducted at the Codo Village Meeting Hall in July 2013. Participants were 18 members of Karang Taruna and Codo village officials. This training received a positive response from Karang Taruna members and the Codo Village community. They felt helped by this training because they could gain new skills that were useful in improving the village economy.